Improving Students’ Speaking Ability Through Video Youtube Channel “Ritueli Daeli” at The Student of MTS Daruttholibin Watumalang - Novicha Lismawati; Niken Kencono Ungu (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to improve students’ speaking skills through the use of the YouTube channel “Ritueli Daeli” among seventh-grade students at MTs Daruttholibin Watumalang. A Classroom Action Research (CAR) approach was implemented in two cycles. Data were collected through interviews, speaking tests, observations, and documentation. The results indicate that incorporating videos from “Ritueli Daeli” significantly enhanced students’ speaking skills in fluency, pronunciation, and confidence. The average score increased from 72.32 in the first post-test to 74.87 in the second post-test, with students’ engagement and motivation visibly increasing. This study supports the integration of digital media, specifically curated YouTube content, as an effective tool to enrich English learning experiences.